A composite with a gradient distribution of graphene and its anisotropic electromagnetic reflection. Issue 6 (20th January 2020) - Zhang, Dayong; Jin, Zhi; Shi, Jingyuan; Peng, Songang; Huang, Xinnan; Yao, Yao; Li, Yankui; Ding, Wuchang; Wang, Dahai
Abstract : An electrochemical method was introduced to prepare graphene/polyurethane foams with gradient graphene distribution, and this composite shows obvious anisotropic reflection of electromagnetic waves. Abstract : So far, it is still difficult to construct composites with a gradient distribution of graphene for decreasing the reflection and increasing the absorption of electromagnetic energy. Here, we introduce an electrochemical method to efficiently prepare a graphene/polyurethane composite with a gradient graphene distribution. And the composite shows obvious anisotropic reflection of electromagnetic waves, with low reflection loss (<−30 dB) and high absorption (>99.5%) in the whole X-band when electromagnetic waves are incident to the surface that has low graphene content. More importantly, the electrochemical method could be extended to the preparation of functional materials with similar structures based on the electrophoresis of charged nanoparticles.